HOW TO REVIVE THE CONSTRUCTION MATERIALS INDUSTRY THROUGH ECONOMIC IMPROVEMENTS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article is focused to the Uzbek construction materials industry's economic resurgence. The research approach is based on a study of the available literature, economic statistics, and research techniques. The study's findings demonstrate the necessity of taking steps including expanding construction investment, enhancing manufacturing technologies, performing marketing research, and raising employee standards in order to revitalize the building materials business.